In situ energy‐dispersive X‐ray diffraction of local phase dynamics during solvothermal growth of Cu4O3. Issue 1 (2nd December 2020) - Jiang, Zhelong; Sharma, Jai; Okasinski, John S.; Chen, Haiyan; Shoemaker, Daniel P.
Abstract : In situ energy‐dispersive X‐ray diffraction was used to track the local formation and conversion of copper oxide phases during solvothermal synthesis. Multi‐valence Cu4 O3 was found to be resistant to chemical conversion once solvothermally precipitated. Abstract : Using in situ methods to characterize the state of a system during reactions is critical to understanding and improving solvothermal syntheses. This work demonstrates the use of in situ energy‐dispersive X‐ray diffraction (EDXRD) to investigate the local dynamics during solvothermal formation of Cu4 O3 using a general‐purpose full‐sized laboratory oven. This allows for direct comparison of in situ data with laboratory‐based reactions. Using in situ EDXRD, changes in the local amounts of Cu4 O3, Cu2 O and CuO within approximately 100 × 100 × 700 µm gauge volumes during solvothermal Cu4 O3 formation were recorded. Fast conversion between Cu2 O and CuO was observed in the solvothermal environment, whereas Cu4 O3 was found to be chemically stable against disturbances once formed. The observed differences in local dynamics give further support to the differences in formation mechanisms between Cu4 O3 and Cu2 O/CuO proposed here.